Fabrication of diverse multicompartment micelles by redispersion of triblock terpolymer bulk morphologies. Issue 35 (26th August 2022) - Quintieri, Giada; Schlattmann, Daniel; Schönhoff, Monika; Gröschel, André H.
Abstract : In this work, we provide guidelines for the formation of multicompartment micelles with defined shapes and inner structure through direct redispersion of terpolymer bulk morphologies in selective, plasticizing solvents. Abstract : Redispersing block copolymer (BCP) bulk films in selective solvents is a simple and efficient method to prepare BCP micelles and polymersomes. While ABC triblock terpolymers are known to form multicompartment micelles (MCMs) with intricate nanoarchitecture, this is typically done by solvent exchange instead of redispersion of bulk films despite obvious advantages of greatly reduced solvent usage. Here, we provide guidelines on how to form MCMs with defined shapes and inner structure through direct redispersion of terpolymer bulk morphologies in selective plasticizing solvents. For this purpose, we redisperse a series of polystyrene- b -polybutadiene- b -poly( tert -butyl methacrylate) (PS- b -PB- b -PT) triblock terpolymers in acetone/isopropanol mixtures, where PT is always soluble, PB always insoluble, and PS will range from soft (high acetone content) to kinetically frozen (high isopropanol content). We investigate the effect of solvent mixtures, block composition, and thermal annealing on MCM shape and core morphology. Additionally, we performed terpolymer blend experiments to open up a simple route to further diversify the range of accessible MCM morphologies.